Mediating role of growth mindset between college life stress and adjustment to college life among nursing students: A-cross sectional study - Sujin Kang; Hye-Ah Yeom (PLoS ONE, 2025)
Adjusting to college life is important for nursing students to achieve academic and work performance successfully. Growth mindset has been proposed as a mediating concept that can induce positive psychological outcomes in stressful life contexts, and may be a potential facilitating factor for adjustment to college life among nursing students experiencing stressful college life. This study aimed to examine the mediating effect of growth mindset in the relationship between college life stress and adjustment to college life in nursing students. This was a cross-sectional descriptive study. The study participants were 250 undergraduate nursing students recruited from three nursing colleges in Korea. Self-reported data on college life stress, growth mindset and adjustment to college life were collected using the online survey questionnaire. The data were analyzed using an independent t-test, one-way ANOVA, Kruskal-Wallis H test, Pearson’s correlation, and multiple regression analysis. The mediating effects were verified through the bootstrapping method using the PROCESS macro for SPSS. Higher levels of adjustment to college life were reported in nursing students who were in good health status and were satisfied with the nursing major. Nursing students’ adjustment to college life was negatively affected by college life stress and positively affected by growth mindset. Growth mindset mediated the link between college life stress and adjustment to college life of nursing students. Educators may be aware that growth mindset can transform stress into challenging opportunities for nursing students. As both types of growth mindset—intelligence and personality—mediated the relationship between college life stress and adjustment to college life, pedagogical strategies cultivating growth mindset in both domains should be developed and implemented to support nursing students’ adjustment.